Administration of vitamin E prevents thymocyte apoptosis in murine sarcoma S180 tumor bearing mice - Liu, D.; Liu, A. (Cellular and Molecular Biology, 2012)
Many reports claimed that thymic involution occurred in tumor bearing host, which led to a reduction of proliferation in T cells and an impaired immune system. In this study, murine sarcoma S180 tumor cells were used to establish tumor model. There was distinct apoptosis in thymus of the S180 tumor bearing host after 3-week tumor inoculation. High level reactive oxygen species generation was detected in thymocytes of S180 tumor bearers. Vitamin E, a potent antioxidant, was oral administrated to S180 tumor bearing mice in order to eliminate redundant ROS in the host and evaluate the effect against thymic apoptosis. Intact thymic structure and less apoptosis of thymocytes demonstrated that partial restoration of thymuses in S180 tumor bearing mice after 3-week VE treatment. Besides, VE treatment normalized ROS level, MDA level and SOD level of S180 tumor bearers. Thus, it could be concluded that thymic involution prevented by VE treatment in S180 tumor bearing mice was mainly due to inhibition of apoptosis in thymus and elimination of ROS over-production in the host.